Biotechnology, Schismogenesis, and the Demise of Uncertainty - Glenn Davis Stone (Washington University Journal of Law & Policy, 2015)
One of the most fundamental aspects of science is uncertainty. Uncertainty fuels scientists to research, experiment, and draw conclusions. Interestingly, both sides of the current “GMO-war” are alleging certainty where it simply does not exist. Through the use of a case study of Bt in India, this Article addresses the irony inherent in both the pro- and anti-GMO arguments based on science that is allegedly foolproof.
Keywords: GMO; uncertainty; science; biotechnology; [Bt]; India